PERTANGGUNGJAWABAN KORPORASI TERHADAP KERUSAKAN LINGKUNGAN DI KABUPATEN MOROWALI - Herlan, Herlan (Katalogis, 2016)
Morowali is a regency that is rich of natural resources. It is evidenced by quite number of mining companies operating there. The total area of Morowali regency is only 14,489.62 Km2 or 1,4 Milion Hectares. However, more than half of the mainland is occupied by concession permits for mining or estate bussines, It was reported by the Morowali Regency Government to the ministry of energy and Minerals Recources that there were 144 valid Mining Bussines Permits (IUP) covering approximately 440.000 hectares. The researcher identified that there were about 27 mining companies cousing environmental problems. One of them was PT. Pnxiang Mining Operating in Siumbatu Village, Bahodopi Sub-District, Morowali Regency, Central Sulawesi Province, failing to comply with environmental assessment statment standards in terms of water pollutions control, air pollutions control, hazardous and poisonousÂ waste treatmentÂ and area demage control. The thesis studies how the criminal lawÂ was enforced in inveronmental cases and how the formulation of criminal accountability was affected to vironmental crimes. It was a normative research to conseptualize and review law as norm, rule and principle or dogma adopted for discussing the main problems proposed based on legal materials and characteristics of legal sciense it self. It was concluded that although the policy on corporate crime accountability formulation in the preavailing environmental Law had provided about subjects of corporate environmental crime, when corporates crime, when corporate crime was commited and who was to b accountable for the crime, it would definetlly need to be more elaborated in order to prevent inconsistent enforcements when applied.